2020
DOI: 10.1039/d0nr02444a
|View full text |Cite
|
Sign up to set email alerts
|

In situ study of the thermal stability of supported Pt nanoparticles and their stabilization via atomic layer deposition overcoating

Abstract: Supported Pt nanoparticle stabilization via Atomic Layer Deposition overcoating with Al2O3 has been proved to prevent particle coarsening during thermal annealing for widely spaced nanoparticles while ensuring surface accessibility for applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…In situ synchrotron grazing incidence small angle X-ray scattering measurements revealed that the ALD Al 2 O 3 stabilizing layer successfully prevented Pt particle from coarsening during thermal annealing and improved the Pt surface accessibility. 87 A selective ALD method was developed to modify Pt NPs with nickel oxide (NiO x ) overcoating to improve the catalytic performance. 88 NiO x can be selectively deposited on the low coordination sites of the Pt NPs during the initial growth period.…”
Section: Applicationsmentioning
confidence: 99%
“…In situ synchrotron grazing incidence small angle X-ray scattering measurements revealed that the ALD Al 2 O 3 stabilizing layer successfully prevented Pt particle from coarsening during thermal annealing and improved the Pt surface accessibility. 87 A selective ALD method was developed to modify Pt NPs with nickel oxide (NiO x ) overcoating to improve the catalytic performance. 88 NiO x can be selectively deposited on the low coordination sites of the Pt NPs during the initial growth period.…”
Section: Applicationsmentioning
confidence: 99%
“…Recent work done by Solano et al utilized ALD to fabricate Pt nanoparticle on a Si substrate to investigate nanoparticle thermal stability as a particle size function . Two different samples were prepared by depositing Pt via ALD using a nucleation regime of either O 2 or N 2 (N 2 *) plasma.…”
Section: Characterizationmentioning
confidence: 99%
“…(b) Representation of particle evolution for Pt–N and Pt–O samples with and without an Al 2 O 3 overcoating. Reproduced with permission from ref . Copyright 2020 Royal Society of Chemistry.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…3j). The negative charge on the surface of NPs has better stability in circulatory system in vivo [31,32]. The LE of PHBV-PTX-NPs, PDA-PHBV-PTX-NPs and RGD-PDA-PHBV-PTX-NPs were 21.48% ± 0.83%, 15.33% ± 0.74% and 14.21% ± 0.66%, respectively.…”
Section: Particle Morphology Size and Zeta Potentialmentioning
confidence: 99%